Kościół i człowiek, lud Boży i komunia. Realizacja Vaticanum II w ujęciu Karola Wojtyły–Jana Pawła II - MARENGO, Gilfredo; KWIATKOWSKI, Krzysztof (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The full implementation of the Vatican II teachings constituted a particularly important theme in the life of the Church in the second half of the 20th century. A crucial stage of this process was the Extraordinary Assembly of the Synod of Bishops convoked in 1985 for the 20th anniversary of the close of the Council and intended to reflect on the process of the reception of the Vatican II. In this context, it seems useful to consider a concept essential for the work of the Synod, namely, that of communio: the Synod reflected upon the central position of this notion, conceived of as the key to the interpretation of Conciliar ecclesiology. On the other hand, it is necessary to appreciate the special attention given by John Paul II to the role of the concept in question and its importance for the crucial points of his teaching. The concept of communio proves particularly appropriate to show that the Church is fully dependent on Christ and His mission in the world. This is true especially in the anthropological-pastoral perspective adopted by John Paul II, who understood communio as the epitome of the Vatican II. Summarized by Patrycja Mikulska